Studi Konstruksi Bagan Apung Milik Nelayan Kelurahan Batu Putih Atas Kota Bitung: Study of the Construction of Floating Fish Aggregating Devices Owned by Fishermen in the Batu Putih Atas Subdistrict, Bitung City - Karyanto; Manohas, Jul; Santoso, Heru; Darondo, Franky Adrian; Katili, Lidya; Putri, Elsari Tanjung (JURNAL ILMU DAN TEKNOLOGI PERIKANAN TANGKAP, 2025)
Bitung City is one of the centers for fisheries production, with the main commodity being capture fisheries, specifically small pelagic fish (mackerel scad (decapterus), mackerel fish (Rastrelliger), tuna (Euthynnus affinis) , and anchovy (Stolephorus indicus)). The purpose of this research is to describe the construction of a floating net cage to support the successful capture of small pelagic fish. The study was conducted from October to December 2024. The data collection methods used were observation and direct interviews with fishermen, and the data were analyzed using qualitative descriptive analysis. The results of the study show that the construction of the lift net includes: a wooden frame measuring 9.5 x 8.5 meters, wooden and net enclosures measuring 3x3 meters, 24 LED lights, a polyethylene net (Cang) measuring 9.5x8.5 meters, a guard house made of wood measuring 2x2 meters, 15 river stones as weights, 4 sand-filled anchors in bags, 12 brass rings, 1 wooden reel, and 24 styrofoam buoy floats.